MEDIATING ROLES OF SCHOOL BELONGINGNESS AND FAMILY FUNCTIONING IN THE RELATIONSHIP BETWEEN CAREER INDECISION AND ACADEMIC PERFORMANCE OF NIGERIAN SECONDARY SCHOOL STUDENTS. - U. Anozie, Emmanuella; E. Eze, John; D. Olabode, Ibini; O. Anozie, Okechukwu (African Journal of Social and Behavioural Sciences, 2024)
Academic performance is widely recognized as an indicator of students’ knowledge improvement and mastery in their fields. However, several factors have been found to impede students’ academic performance, preventing them from reaching their goals. This study investigated the relationship between career indecision and academic performance and whether this relationship is mediated by school belongingness and family functioning. The study adopted a cross-sectional design. Participants were 1408 secondary school students (males = 827, 58.7%; females = 581) drawn from 11 secondary schools from four states in Southeast Nigeria using a multi-stage sampling method. The mean age of the participants was 15.50 years (SD = 1.27 years). They completed the Psychological Sense of School Membership Scale, Family APGAR questionnaire and Career Decision-Making Difficulties Questionnaire. Data on academic performance were obtained from the student’s report cards from the previous third-term examinations in their various schools, which is usually a summation of the session’s performance. Data was analysed using Pearson’s correlation and Model 4 of the Hayes PROCESS Macro in SPSS. Results indicated that school belongingness and family functioning were positively associated with academic performance, while career indecision was negatively associated with it. Further, results indicated that the relationship between career indecision and academic performance was mediated by school belongingness but not family functioning. It was recommended that intervention programs that aim to improve students’ academic performance be incorporated to improve students’ sense of school belonging, family functioning, and career indecision.